PERFORMA PERTUMBUHAN CALON INDUK IKAN GABUS Channa striata YANG DIBERI PAKAN BENIH IKAN NILA Oreochromis sp.: Growth Performance of Snakehead Fish Channa striata Broodstock Feeding By Tilapia Seeds Oreochromis sp. - M. Muslim; Andri Iskandar; Andri Hendriana; L. Lutfi (IPB University, 2021)
ABSTRACTThe purpose of this study was to determine the growth of parent stock snakehead fish Channa striata in a pond fed with tilapia Oreochromis sp. seeds using different feeding rates. Studies were carried out using three different treatments feeding rate (FR), which is 2%, 3%, and 4%. The parameters observed included growth, feed conversion ratio, and water quality. The results showed that the growth of the average weight of fish FR 4% per day (growth rate 86,01 g) had higher than other treatments. The value of feed conversion is 2,5 while the fish is given FR 2%. Parameters of water quality, i.e. pH, temperature, alkalinity, and ammonia still in the range of tolerance.